Critical Remarks on Roman Law in the Prussian Correction - Lisowski, Zygmunt (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The paper is an English translation of O prawie rzymskim w korekturze pruskiej. Uwagi krytyczne by Zygmunt Lisowski, published originally in Polish in “Czasopismo Prawno–Historyczne” in 1954. The text is pub-lished as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Faculty of Law and Administra-tion” devoted to the achievements of the late Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.